1994
DOI: 10.4319/lo.1994.39.5.1020
|View full text |Cite
|
Sign up to set email alerts
|

Determination of phytoplankton crops by top‐down and bottom‐up mechanisms in a group of English lakes, the West Midland meres

Abstract: Twenty-four lake basins formed in glacial drift ranged in maximum depth from 1.5 to 3 1 m and were characterized by generally low inorganic N concentrations and very high total P concentrations. The high P values were in some cases related to farm effluent pollution but in many others, despite annual mean values up to 1.46 mg liter-I, appear natural and due to the local mineralogy.For the entire group, there were no significant relationships between mean growth season chlorophyll a concentration and any measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
79
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 20 publications
3
79
0
2
Order By: Relevance
“…Nevertheless, the Daphnia behaviors we documented are consistent with the suggestion by Moss et al (1994) that macrophytes are important refuges for large zooplankton in shallow lakes and allow zooplankton to suppress phytoplankton abundance even in the presence of zooplanktivorous fish. Abstract-The feeding-deterrent properties of a suite of common holoplankton (nine species representing five phyla) collected from oceanic waters near Bermuda were investigated.…”
supporting
confidence: 77%
“…Nevertheless, the Daphnia behaviors we documented are consistent with the suggestion by Moss et al (1994) that macrophytes are important refuges for large zooplankton in shallow lakes and allow zooplankton to suppress phytoplankton abundance even in the presence of zooplanktivorous fish. Abstract-The feeding-deterrent properties of a suite of common holoplankton (nine species representing five phyla) collected from oceanic waters near Bermuda were investigated.…”
supporting
confidence: 77%
“…In addition to the reservoir temperature, transparency, pH and alkalinity also showed positive correlation with the planktons' diversity and abundance in the reservoir water. While P is considered as the prime nutrient that limits primary productivity in lakes and reservoirs [45] [46], numerous studies have shown that the biomass of phytoplanktons can be nitrogen-limited [39] [47]. The relatively higher concentrations of phosphate than nitrate, observed in the present study, indicates that the plankton's density in the reservoir was mainly the function of N. In general, inorganic forms of N and P were usually depleted in spring very rapidly and their concentrations remain at the low level till late autumn.…”
Section: Plankton Distributionmentioning
confidence: 99%
“…Conductivity is high (300-350 s cm Ϫ1 ), alkalinity is moderate (1.7 Ϯ 0.1 meq liter Ϫ1 , and pH ranges from 6.7 to 9.8. Soluble reactive and total phosphorus concentrations span 0.5 to Ͼ1.0 mg liter Ϫ1 , which is not atypical of stratified meres in the region (Reynolds 1971; Moss et al 1994Moss et al , 1997. There are no point sources of eutrophication and no surface inflows.…”
mentioning
confidence: 99%